Students’ experiences on leadership and motivation in group works - Sabariah Abd Rahim; Saifulazry Mokhtar; Irma Wani Othman; Mohd Sohaimi Esa; Romzi Ationg (Global Academic Excellence, 2023)
Completing a group assignment may be difficult if group members are uncooperative. Therefore, it is essential for group assignments to have an effective leader who can manage group members through group work. Regarding this, this study seeks to examine the leadership and motivational experiences of students engaged in group work. The study employed a qualitative case study approach, and the data for this study were gathered through individual interviews with ten students selected by purposive sampling. The results of this study indicate that the ten students who participated in group work activities had positive leadership and motivational experiences, including defined roles and responsibilities as well as enhanced confidence and communication skills. This study provides insight into the leadership and motivational experiences of L2 students that contributed to the success or failure of group work in a classroom.